PENGARUH INVENTARISASI, PEMBUKUAN DAN PELAPORAN ASET TERHADAP AKUNTABILITAS PUBLIK PEMERINTAH DAERAH - Imbiri, Jefri; Rofingatun, Siti; Pangayow, Bill J. C. (Fakultas Ekonomi, Universitas Cenderawasih, 2018)
This study aims to examine the effect of Bookkeeping, Inventory and Reporting of Assets on the Public Accountability of the Waropen District Government. Respondents in this study were 50 people who were employees who had knowledge about asset utilization and the staff in charge of managing regional goods. The analysis tool in this study uses SPSS with this type of research that is causality which tests the effect of independent variables on dependent so that researchers use Multiple Regression Analysis. Which results of this study must meet the Classical Assumption Test, namely the Normality Test, Multicollinearity Test and Heterocytes Test. Therefore, the results of this study indicate that simultaneously the accounting, inventory and reporting variables influence public accountability with a significance value of 0,000. However, partially the inventory has an effect on public accountability with a significance value of 0.035. While partially Asset Accounting and Reporting does not affect public accountability with a significance value of 0.078 and 0.071, Bookkeepingrespectively.